The Spread of Plasticity in High-Strength Reinforced Concrete Structural Walls with Boundary Elements. - Egleston, Erik. (2017)
Abstract: Eight new large-scale tests of reinforced concrete structural walls with highly confined boundary elements, conducted at Michigan State University (MSU), demonstrate that the bond stress flexure-shear model for assessing Lpr, Lp and displacement, developed by Hines et al., may be extended to concrete strengths up to 20 ksi and monotonic loading. Improving the model of strain penetration to account for the laterally post-tensioned footings used by the MSU tests doubles the accuracy of the prediction of Lp. Modifying the experimental calculation of Lp to account for particularities of the MSU tests reveals the potential accuracy of the flexure-shear model. For the MSU tests, excluding the effect of concrete tension results in a minimal increase in error when predicting Lpr, Lp and displacement. Analysis of a set of parametric models shows that the increase in error when predicting Lp and displacement is less than 10% provided that the longitudinal reinforcement ratio in the boundary element is greater than 3% for up to 10 ksi concrete, and 4% for up to 20 ksi concrete.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Civil Engineering.; Advisor: Eric Hines.; Committee: Masoud Sanayei, and Rigoberto Burgueño.; Keyword: Civil Engineering.